The assessment of the structure of anti-doping rules violation and the evaluation of anti-doping measures efficiency in Russian athletics during 2000-2020 - E. N. Bezuglov; O. B. Talibov; V. Y. Khaitin; A. M. Lazarev (National Electronic Information Consortium (NEICON), 2021)
The assessment of the structure and trends of doping perpetrations among athletes with a proven high prevalence of doping use might be of great practical interest. Non-compliance with the zero-tolerance policy towards anti-doping rules violators among sports communities with a high prevalence of doping offenses is the main cause of the ineffective fight against doping.Objective: to analyze the structure of anti-doping rule violations and evaluate the effectiveness of measures to counter the spread of doping in Russian athletics in 2000-2020.Materials and methods: to form an objective picture, a database was collected on all anti-doping rule violators in Russian athletics from 2000 to June 01, 2020 from open sources. Retrospective analysis of the protocols of all official competitions held in Russia since 2000 and included in the RUSAF Unified Schedule was performed.Results: 381 cases of anti-doping rule violation committed during 2000-2020 period by 355 athletes were registered. 25 athletes committed 2 doping offenses and 1 athlete 3 ones. Women perpetrated more offenses than men.Conclusions: our study objectified the doping issue in Russian athletics and evaluated the effectiveness of anti-doping measures. The study indicates the need to stop ignoring zero-tolerance policy principles towards doping offenders among the athletic community and creates an incentive to develop functional mechanisms to combat doping.